2004
DOI: 10.1177/070674370404900910
|View full text |Cite
|
Sign up to set email alerts
|

Social Phobia among University Students and its Relation to Self-Esteem and Body Image

Abstract: The results show that persons with social phobia have lower self-esteem and more distorted body image than do those without social phobia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
78
1
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(99 citation statements)
references
References 12 publications
8
78
1
5
Order By: Relevance
“…It is reported in some studies that suicide is more frequent in rural areas and especially firearms suicides are significantly more common (43,44). Being born in village or at least 15 years living in village have been identified with a high prevalence of social phobia in a national study (45). In some studies, it was reported that conversion disorder symptoms are more common with people from rural areas and from lower socio-cultural levels (46,47) and again in a national survey, it is found that somatoform disorders are significantly more often in rural (18).…”
Section: Discussionmentioning
confidence: 99%
“…It is reported in some studies that suicide is more frequent in rural areas and especially firearms suicides are significantly more common (43,44). Being born in village or at least 15 years living in village have been identified with a high prevalence of social phobia in a national study (45). In some studies, it was reported that conversion disorder symptoms are more common with people from rural areas and from lower socio-cultural levels (46,47) and again in a national survey, it is found that somatoform disorders are significantly more often in rural (18).…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with Mirza et al 24 we observed that body image anxiety was common among perceived overweight. Izgic et al 25 observed that body image anxiety was associated with social phobia. Similar result was appreciated in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Izgic et al found the one year prevalence of social phobia in university students to be 7.9% and life-time prevalence to be 9.6% which is similar to our results. 14 Studies in different countries have placed the prevalence of social phobia in the range of 5% to 8%, making it the most common anxiety disorder and one of the most common psychiatric disorders. [15][16] A lower prevalence rate was noted in German adolescents in the 14 to 15 year old group (2%) and 16 to 17 year old age group (2%).…”
Section: Discussionmentioning
confidence: 99%